2021
DOI: 10.1177/20451253211014320
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma VEGF levels and the antidepressant effects of ketamine in patients with depression

Abstract: Aims: Growing evidence suggests that vascular endothelial growth factor (VEGF) may be involved in the neuronal mechanisms underlying both depression aetiology and the response to ketamine treatments. The aim of this study was to examine whether changes in plasma VEGF levels are associated with the antidepressant effects of repeated ketamine infusions in patients with depression. Methods: Ninety-six patients with depression were enrolled and received six ketamine infusions during a 12-day period. Depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…However, our data failed to demonstrate that plasma VEGF concentrations were significantly associated with ketamine's rapid antianhedonic effects in subjects with TRD. Similarly, a recent study also found that VEGF does not play a critical role in the observed antidepressant response to ketamine in depressed patients (24). However, the association of VEGF and ketamine's antisuicidal effects is unclear.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, our data failed to demonstrate that plasma VEGF concentrations were significantly associated with ketamine's rapid antianhedonic effects in subjects with TRD. Similarly, a recent study also found that VEGF does not play a critical role in the observed antidepressant response to ketamine in depressed patients (24). However, the association of VEGF and ketamine's antisuicidal effects is unclear.…”
Section: Discussionmentioning
confidence: 95%
“…All blood samples of seventy-eight subjects with treatment-refractory MDD or BD were collected preinfusion and again at days 13 and 26. Consistent with a recent study ( 24 ), a Human VEGF Immunoassay enzyme-linked immunosorbent assay (ELISA) kit (R&D Systems, Minneapolis, USA) was used to measure the plasma concentrations of VEGF.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Deyama et al found that the rapid antidepressant response to ketamine was associated with neuronal VEGF-Flk-1 signaling in the medial prefrontal cortex (mPFC) ( 28 ). Finding on the relationship between VEGF and ketamine's antidepressant effect in depressed patients were inconsistent ( 29 , 30 ). For instance, McGrory et al found that VEGF plays an essential role in the antidepressant action of ketamine ( 30 ).…”
Section: Introductionmentioning
confidence: 99%